EMPLOYEE ATTENDANCE INFORMATION SYSTEM AT BERKAH TRANSLATOR WEB-BASED - Mutqi Amrillah; Dwi Arif Wibowo; Revaldy Dwi Putra (Lembaga Pengembangan Kinerja Dosen, 2022)
In the modern environment, it is challenging to distinguish daily activities and employment from the usage of digital technology. This web-based employee attendance information system was designed to make it simpler for administrators and employees to keep track of attendance and recapitulation considering the importance and necessity of attendance for a business or institution. This information system has forms for employees to complete in order to view their attendance and notes, such as my attendance, add notes, and my notes. I developed this web-based information system with the assistance of php myadmin, notepad ++, dreamweaver, and visual studio. As a consequence of the research, an online employee attendance tracking system may boost company performance, particularly in the field of human resources.